A new name for an old problem—Colletotrichum cigarro is the cause of St John’s wilt of Hypericum perforatum - Kreth, Lana-Sophie; Damm, Ulrike; Götz, Monika (Frontiers in Fungal Biology, 2025)
A major problem for St John’s wort (Hypericum perforatum) is St John’s wilt, which can lead to reduced crop yields and even complete crop losses. In the past, the pathogen was referred to as Colletotrichum gloeosporioides or occasionally as Colletotrichum cf. gloeosporioides based on morphology. Although a strain from this host had been re-identified as C. cigarro in taxonomic studies, there is uncertainty about the identity of the St John’s wilt pathogen, which is generally still addressed as C. gloeosporioides in applied science. In a multi-locus [internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), actin (ACT), and glutamine synthetase (GS)] analysis of the C. gloeosporioides species complex, all isolates obtained from newly collected symptomatic H. perforatum stems and seeds from Germany and Switzerland were identified as C. cigarro. Although they belonged to the same haplotype, the morphology of the isolates was very variable. Pathogenicity tests demonstrated that only C. cigarro strains from H. perforatum cause symptoms on H. perforatum, whereas other Colletotrichum species tested only caused latent infection of H. perforatum.